2017
DOI: 10.1016/j.jinsphys.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of entomopathogenic fungal culture filtrate on the immune response of the greater wax moth, Galleria mellonella

Abstract: Galleria mellonella is a well-established model species regularly employed in the study of the insect immune response at cellular and humoral levels to investigate fungal pathogenesis and biocontrol agents. A cellular and proteomic analysis of the effect of culture filtrate of three entomopathogenic fungi (EPF) species on the immune system of G. mellonella was performed. Treatment with Beauveria caledonica and Metarhizium anisopliae 96h culture filtrate facilitated a significantly increased yeast cell density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…The fact that the EPF of the different fungal species alters different members of these cascades may explain the different levels of immunomodulation observed in the cellular bioassays. Interestingly similar observations were made by Mc Namara et al (2017) who showed that the filtrate of M. brunneum and B. caledonica also altered the abundance of serine proteases and serpins in the haemolymph of G. mellonella larvae highlight potentially conserved immunomodulatory effects of the excretory/secretory products of entomopathogenic fungi.…”
Section: Epf Culture Filtrate Alters Abundance Of Serine Proteases Ansupporting
confidence: 79%
See 1 more Smart Citation
“…The fact that the EPF of the different fungal species alters different members of these cascades may explain the different levels of immunomodulation observed in the cellular bioassays. Interestingly similar observations were made by Mc Namara et al (2017) who showed that the filtrate of M. brunneum and B. caledonica also altered the abundance of serine proteases and serpins in the haemolymph of G. mellonella larvae highlight potentially conserved immunomodulatory effects of the excretory/secretory products of entomopathogenic fungi.…”
Section: Epf Culture Filtrate Alters Abundance Of Serine Proteases Ansupporting
confidence: 79%
“…. mellonella larvae injected with M. brunneum and B. caledonica there were alterations in abundance of peptidoglycan recognition-like (due to M. brunneum) and β-1,3-GBP and two peptidoglycan recognition proteins (due to B. caledonica)(Mc Namara et al 2017). Insects can differentiate between major groups of microbes using pattern recognition receptor (PRRs) such as PGRPs, hemolin and β-1,3-GBP.…”
mentioning
confidence: 99%
“…Among these models, the facile inoculum delivery and handling of G. mellonella makes it a desirable model for the study of fungal pathogenesis (Fuchs et al 2010;Junqueira 2012). Furthermore, the immune system of G. mellonella possesses a number of structural and functional similarities to the innate immune system of mammals (Bergin et al 2003;Bergin et al 2006;Mc Namara et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Treated the larvae of E. insulana and P. gossypiella using T. harzianum spores caused moderately high mortality for insect treatment, respectively (El-Massry et al, 2016). Others reported that B. bassiana can be used as biocontrol agents, the treated of G. Mellonella with culture filtrate of B. caledonica and M. anisopliae showed a significant increased larval mortality (Namara et al, 2017).…”
Section: Se = Standard Errormentioning
confidence: 99%
“…(2014). In Egypt, it was found that T. harzianum liquid filtrate and spores had to produce a large mortality rate and caused significant reduction in adult emergence significant effect on the larvae of Earias insulana and Pectinophora gossypiella caused more mortality rate for the tested insects (El-Massry et al, 2016).The treated G. mellonella with B. caledonica and M. anisopliae caused a significantly increased yeast cell density and increased larval mortality (Namara et al, 2017). Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%